Application of information graphics in visualizing data through local newspaper / Anith Liyana Amin Nudin - Amin Nudin, Anith Liyana (2011)
The very wide world of information keeps on buzzing our minds day by day. From types of food we consume, the amount of employees that have been retrenched, the total SMS votes for a reality show on TV, the average hours spent on the road, and even from the garbage that we throw, all of these information are being communicated through various media, including newspaper. Diagrams, charts, maps or any visual aids or currently known as infographic, is defined as a visual language in delivering information at ease. As for Malaysia, some designers might have aware of the rising issues of information design and infographics but getting chance to apply the knowledge in the real industry is very thin for now. Daily newspapers are believed to establish the application of infographics just like USA today and New York times did 2-3 decades ago, and the trend went wide spreading to various media and purposes. The need in converging towards visual-oriented newspaper by using infographics is crucial, seems the world is gradually moving from a textbased to a visually-oriented society. Applying infographic to economical data in ‘Laporan Ekonomi’ is potential to manifest that it is able to encourage and enhance the readability of statistical data, besides opening the eyes of readers in reading visually. Overview, the emergence of welldesigned infographics is very crucial in Malaysia to spark a new, competitive design dimension for designers besides contributing towards visual-oriented society.